Headache, anxiety and depressive disorders: the HADAS study - Beghi, Ettore (Springer Milan, 2010)
The objective of this paper was to assess prevalence and characteristics of anxiety and depression in migraine without aura and tension-type headache, either isolated or in combination. Although the association between headache and psychiatric disorders is undisputed, patients with migraine and/or tension-type headache have been frequently investigated in different settings and using different tests, which prevents meaningful comparisons. Psychiatric comorbidity was tested through structured interview and the MINI inventory in 158 adults with migraine without aura and in 216 persons with tension-type headache or migraine plus tension-type headache. 49 patients reported psychiatric disorders: migraine 10.9%, tension-type headache 12.8%, and migraine plus tension-type headache 21.4%. The MINI detected a depressive episode in 59.9, 67.0, and 69.6% of cases. Values were 18.4, 19.3, and 18.4% for anxiety, 12.7, 5.5, and 14.2%, for panic disorder and 2.3, 1.1 and 9.4% (p = 0.009) for obsessive–compulsive disorder. Multivariate analysis showed panic disorder prevailing in migraine compared with the other groups (OR 2.9; 95% CI 1.2–7.0). The association was higher (OR 6.3; 95% CI 1.4–28.5) when migraine (with or without tension-type headache) was compared to pure tension-type headache. This also applied to obsessive–compulsive disorder (OR 4.8; 95% CI 1.1–20.9) in migraine plus tension-type headache. Psychopathology of primary headache can reflect shared risk factors, pathophysiologic mechanisms, and disease burden.